Draft Genome Sequence of Tolypothrix boutellei Strain VB521301 - Chandrababunaidu, Mathu Malar (Genome Announc, 2015)
We report here the draft genome sequence of the filamentous nitrogen-fixing cyanobacterium Tolypothrix boutellei strain VB521301. The organism is lipid rich and hydrophobic and produces polyunsaturated fatty acids which can be harnessed for industrial purpose. The draft genome sequence assembled into 11,572,263 bp with 70 scaffolds and 7,777 protein coding genes.